On the Solvency of Nations: Cross-Country Evidence on the Dynamics of External Adjustment - C. Bora Durdu; Enrique G. Mendoza; Marco E. Terrones (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
We test the hypothesis that net foreign asset positions are consistent with external solvency and examine the dynamics of external adjustment using data for 50 countries over the 1970-2006 period. Our analysis adapts Bohn's (2007) error-correction reaction function approach - which tests for a negative long-run relationship between net exports (NX) and net foreign assets (NFA) as a sufficiency condition for the intertemporal budget constraint to hold - to a dynamic panel framework. Pooled Mean Group (PMG) and Mean Group error-correction estimation yield evidence of a statistically significant, negative response of NX to NFA. Moreover, we cannot reject the hypothesis that the response is largely homogeneous across countries. Our sensitivity analysis shows that the countries with relatively weaker fundamentals need to respond more strongly to the changes in NFA to keep their NFAs on a sustainable path.
Keywords: F41; F32; E66; 330; global imbalances; external solvency; debt sustainability; Pooled Mean Group estimation; Außenwirtschaftliches Gleichgewicht; Internationale Staatsschulden; Nachhaltigkeit; Auslandsvermögen; Sensitivitätsanalyse; Schätzung; Welt